Concise guide to neuropsychiatry and behavioral neurology - Cummings, Jeffrey L; Trimble, Jeffrey L (American Psychiatric Publishing, 2002)
West Los Angeles Veterans Affairs Medical Center, California. Pocket-sized manual for psychiatrists, residents, and medical students to the evaluation and management of patients with both neurological and psychiatric disorders.
Concise guide series
Keywords: Mental Disorders; Brain Diseases; neuropsychologie; neurovědy; duševní poruchy; psychiatrie; zdravotně postižení; Neuropsychology; nemoci mozku